Study on permanent deformation properties of construction waste soil under traffic loading - Li, Chenchen; Zhang, Chuang; Weng, Hui; Qin, Yaodong; Shang, Huayu; Zhang, Junhui (Frontiers in Materials, 2025)
The permanent deformation characteristics of subgrade filler under cyclic loading are the key factors affecting the long-term stability of subgrade and pavement performance. This study aims to systematically analyze the permanent deformation characteristics of construction waste soil as subgrade filler under cyclic loading through dynamic triaxial tests to optimize roadbed design and extend its service life. Results indicate that confining pressure, moisture content, and dynamic stress amplitude significantly affect permanent deformation. Specifically, increasing confining pressure from 60 kPa to 120 kPa reduces permanent deformation by 40%, while increasing moisture content from 0.8 to 1.2 times the optimum moisture content increases deformation by 36%. The dynamic stress amplitude is increased from 40 kPa to 130 kPa, and the deformation is increased by 263%. Based on the experimental data, the prediction model of permanent deformation of subgrade filler is established, and the prediction accuracy and universality of the model are verified by comparing with the experimental data of this study and other existing literature. The model can provide a scientific basis for subgrade design and help to select construction parameters reasonably, so as to effectively control the permanent deformation of subgrade and reduce maintenance costs.